EXPERIENCE OF MEASURING THE LEVEL OF VICTIMIZATION OF THE POPULATION OF NIZHNIY NOVGOROD REGION - A. A. Glukhova; A. A. Iudin; D. A. Shpilev (Russian Journal of Economics and Law, 2016)
Objective: basing on the data from empirical sociological study, to identify the level of latency and victimization of the population ofNizhny Novgorod region.Methods: general scientific (analysis, systemic-structural approach to the analysis of object of research, comparative-legal) as well as logical methods and specific scientific method (survey - questionnaires and interviews).Results: qualitative and quantitative analysis is performed of the overall situation referring to unrecorded crime (latent crime), committed on the territory of Nizhny Novgorod city and Nizhny Novgorod oblast, as well as comparative analysis of the level of latent crime in the city and region by the types and trends of criminal activities; the main reasons are identified for refusal the victims to appeal to police in Nizhny Novgorod and Nizhny Novgorod oblast; recommendations and proposals are elaborated of the work of territorial bodies of the Ministry of Domestic Affairs to the aim of reducing the level of latent crime.Scientific novelty: for the first time on the basis of data obtained during a sociological survey, the crime situation on the territory of Nizhny Novgorod region is discussed, revealing the actual level of latent delinquency, and proposals and practical recommendations are formulated for the adjustment of the work of territorial bodies of the Ministry of Domestic Affairs to the aim of reducing the level of latent crime. Practical significance: basing on the research, the recommendations are to improve the work of territorial bodies of the Ministry of Domestic Affairs to the aim of reducing the level of latent crime.